Radiographic Evaluation of Fractured and Non-Fractured Metacarpal Bones in Holstein Calves Subjected to Pulling during Dystocia - Akin, Ibrahim; Sevil-Kilimci, Figen; Yaygingul, Rahime; Bardakcioglu, Husnu Erbay (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective This study aimed to investigate the transverse cortical cross-sections of the metacarpal bones of newborn calves subjected to pulling during dystocia.Materials and Methods In total, radiographs of 63 metacarpal bones (35 fractured and 28 non-fractured) of 50 Holstein calves were evaluated in this study. According to the declaration of the owners, all calves were pulled by their metacarpal bones during parturition.The periosteal and endosteal diameters, medial and lateral cortical thicknesses and dorsal and palmar cortical thicknesses were measured. Furthermore, the total, cortical and medullary areas of each section, moments of inertia on the X and Y axes, major and minor principal moments of inertia, angle of rotation of the axis and polar moment of inertia were calculated. The data were analysed by sex and body weight.Results Body weight did not affect the bone status. However, females had a 6.5 times higher risk of bone fracture as compared with the males (p = 0.001). The lateral cortical thickness of the fractured bones in the female animals was thinner than that of the male animals (p = 0.001).Conclusion These results can be used to improve dystocia manipulations, encourage the development of new tools for dystocia and the treatment of metacarpal fractures in calves.
Keywords: calf; cross-sectional geometry; dystocia; metacarpal fractures; radiographs